Does it pay to read your junk mail? Evidence of the effect of advertising on home equity credit choices - Sumit Agarwal; Brent W. Ambrose (Federal Reserve Bank of Chicago, 2008)
We examine the effect of direct mail (commonly referred to as junk mail) advertising on individual financial decisions by studying consumer choice of home equity debt contracts. Consistent with the theoretical predictions, we find that financial variables underlying the relative pricing of debt contracts are the leading factors explaining consumers' home equity debt choice. Furthermore, we also find that the intended use of debt proceeds significantly impacts consumer choice. However, when we study a subset of consumers who received a direct mail solicitation for a particular debt contract (fixed- versus adjustable-rate), we find evidence that the relative pricing variables are less relevant in explaining consumer contract choice, even though they were presented with a full menu of debt contracts. Thus, our results are consistent with the view that advertising is persuasive.
Keywords: D1; D8; G21; M3; 330; Persuasion; Advertising; Contract Choice; Home Equity Lending; Direktwerbung; E-Mail; Konsumentenverhalten; Werbewirkung